5. PROSES PERUBAHAN POLITIK DI MYANMAR: MENUJU DEMOKRASI MELALUI PEMILIHAN UMUM - Nilasari, Yolanda Utami (FORUM, 2014)
After being a closed country for many years before, Myanmar is finally become more open to international community. Election as the one of the significant value of democracy is using to indicate that Myanmar started to have democracy in their country. This action has succeced to change some of international's community opinions and policies concerning this country.